Political Capital Strategies In Sherly Tjoanda’s Victory In The 2024 North Maluku Governor Election - La Ode Muhammad Adam Nur (International journal of technology and education research, 2026)
This study aims to analyze the political capital strategies employed by Sherly Tjoanda in winning the 2024 North Maluku Governor and Deputy Governor Election through the lens of Pierre Bourdieu’s theory of capital. This study employs a qualitative descriptive approach using the case study method. Data collection techniques included interviews, observations, and documentation. The analysis was conducted using the concepts of economic capital, social capital, cultural capital, and symbolic capital proposed by Pierre Bourdieu and reinforced by Robert Putnam’s theory of social capital. The results indicate that Sherly Tjoanda’s victory was not determined solely by electoral support but was the result of the accumulation and conversion of various forms of capital she possessed. Economic capital played a role in supporting the effectiveness of the campaign and political mobilization. Social capital was evident in the strength of political networks, support from elites and community leaders, and the high level of public trust formed through bonding social capital and bridging social capital. Cultural capital was reflected in political communication skills, leadership capacity, and the articulation of development programs aligned with community needs. Meanwhile, symbolic capital emerged as the most dominant factor through the social legitimacy derived from Sherly Tjoanda’s image as a female leader and the successor to Benny Laos’s political legacy. The findings of this study indicate that success in local political contests is heavily influenced by political actors’ ability to effectively manage and convert various forms of capital within the political arena.